Model Pesantren Berbasis Industri dan Pinter Ngaji - Omay Komarudin; Nurwadjah Ahmas; Andewi Suhartini (STIT Al-Quraniyah Manna, 2021)
The purpose of writing this article is to inspire a pesantren that can solve the problems of unemployment, weak character and weak mastery of religious science so that it becomes a model for industrial-based Islamic boarding schools and good at religion. The research method used is qualitative with a descriptive study approach to the research locus. The research instrument used was observation, interviews, and library research as well as supporting documents for this research. The results showed that the creation of international expertise skills was able to attract the employing industry with decent rewards, even the industry ordered IDN alumni, the cultivation of strong characters with 9 characters proved that students had the character of maturity, tough, champion, independent and visoner and useful character, by planting The religious practices that are practiced on a daily basis make the students have a handle on life and be able to worship daily properly.